Resource limitation, tolerance, and the future of ecological plant classification - Craine, Joseph M.; Engelbrecht, Bettina M.; Lusk, Christopher H.; McDowell, Nate; Poorter, Hendrik (Frontiers in Plant Science, 2012)
Throughout the evolutionary history of plants, drought, shade, and scarcity of nutrients have structured ecosystems and communities globally. Humans have begun to drastically alter the prevalence of these environmental factors with untold consequences for plant communities and ecosystems worldwide. Given limitations in using organ-level traits to predict ecological performance of species, recent advances using tolerances of low resource availability as plant functional traits are revealing the often hidden roles these factors have in structuring communities and are becoming central to classifying plants ecologically. For example, measuring the physiological drought tolerance of plants has increased the predictability of differences among species in their ability to survive drought as well as the distribution of species within and among ecosystems. Quantifying the shade tolerance of species has improved our understanding of local and regional species diversity and how species have sorted within and among regions. As the stresses on ecosystems continue to shift, coordinated studies of whole-plant growth centered on tolerance of low resource availability will be central in predicting future ecosystem functioning and biodiversity. This will require efforts that quantify tolerances for large numbers of species and develop bioinformatic and other techniques for comparing large number of species.